2017
DOI: 10.1101/149369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An open resource for transdiagnostic research in pediatric mental health and learning disorders

Abstract: Technological and methodological innovations are equipping researchers with unprecedented capabilities for detecting and characterizing pathologic processes in the developing human brain. As a result, ambitions to achieve clinically useful tools to assist in the diagnosis and management of mental health and learning disorders are gaining momentum. To this end, it is critical to accrue large-scale multimodal datasets that capture a broad range of commonly encountered clinical psychopathology. The Child Mind Ins… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
205
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(206 citation statements)
references
References 82 publications
0
205
0
1
Order By: Relevance
“…In our study, we showed a highly reproducible white matter parcellation using the fiber clustering method; thus, we suggested this method could be reproducibly applied for clinical applications and large dataset analysis. These applications can include white matter parcellation for neurosurgical planning (O'Donnell et al, ), parcellation of scans from different time points to track white matter changes, and analysis of very large diffusion MRI datasets that will soon become available (Alexander et al, ; Casey et al, ; Thompson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we showed a highly reproducible white matter parcellation using the fiber clustering method; thus, we suggested this method could be reproducibly applied for clinical applications and large dataset analysis. These applications can include white matter parcellation for neurosurgical planning (O'Donnell et al, ), parcellation of scans from different time points to track white matter changes, and analysis of very large diffusion MRI datasets that will soon become available (Alexander et al, ; Casey et al, ; Thompson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A low relative difference (RD) value represents a high test-retest reproducibility. The tracts with significantly lower mean relative difference scores using the fiber clustering method are annotated with a red asterisk, while the tracts with significantly lower mean relative difference scores using the cortical-parcellation-based method are annotated with a blue X [Color figure can be viewed at wileyonlinelibrary.com] white matter parcellation for neurosurgical planning , parcellation of scans from different time points to track white matter changes, and analysis of very large diffusion MRI datasets that will soon become available (Alexander et al, 2017;Casey et al, 2018;Thompson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child Mind Institute -Healthy Brain Network (CMI-HBN). Data were collected from 523 participants (ages 6.0-17.0 year old, mean age 10.3; M:F 309:214) of the CMI-HBN (Alexander et al, 2017), which is designed to recruit a sample of 10,000 children and adolescents from the New York City area, collected using a community self-referred model that recruits participants based on the presence of behavioral concerns. Testing correspondence between E-SWAN and traditional scales.…”
Section: Participantsmentioning
confidence: 99%
“…Abnormalities in such functional development have been linked to neurological disorders or psychiatric diseases (Chase, ; Park et al, ). To further understanding of the maturation of functional networks, an increasing number of neuroimaging studies are acquiring longitudinal rs‐fMRI (Alexander et al, ; Kooijman et al, ; Nora et al, ). For example, the multi‐site National Consortium on Alcohol and NeuroDevelopment in Adolescence (NCANDA) study (Brown et al, ; Müller‐Oehring et al, ; Pfefferbaum et al, ; Sullivan et al, ) is investigating adolescent neurodevelopment and its deviation due to alcohol use by acquiring rs‐fMRI of each study participant before initiating appreciable drinking and following them annually.…”
Section: Introductionmentioning
confidence: 99%